A Halomonas cupida strain stimulates Chlorella vulgaris in a eutrophic environment: Elevated biomass yield and photosynthetic performance - Ning Ding; Fan-Qiang Yan; Zheng-Qi Wang; Qian-En Zhu; Chun-Chen Liu; Pei-Ke Gao; Ren-Jun Wang (Estuarine, Coastal and Shelf Science, 2026)

Feasibility of producing specific pathogen-free gibel carp (Carassius auratus gibelio var. CAS III) by selective breeding of Myxobolus honghuensis-free broodstock - En Bang Shao; Fan Zhou; Li Qiang Zhang; Jian Chun Shao; Yang Liu (Aquaculture, 2026)

A Model-based Harmonization Strategy of Standard Uptake Values for Paired PET Studies - Tian Mou; Yuejie Lin; Fanghui Fan; Jian Huang; Taotao Sun; En-Tao Liu; Yi Gao (Phenomics, 2026)

Bioactivity-guided isolation of alkaloids and chlorophyll-derived compounds from Murraya koenigii with anti-inflammatory, anti-allergic, and SARS-CoV-2 entry-inhibitory activities - Mohamed Abbas Umare Faruk; Michal Korinek; Keerthana Shanmuganathan; Soundar Rajan Kulandhaivel; Sheng-Fan Wang; En-Liang Chu; Hui-Chun Wang (Food Bioscience, 2026)

Corrigendum to: “Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury” [Chem. Eng. J. 524 (2025) 169698] - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2026)

Plant presence fundamentally alters soil microbial and biogeochemical responses to polylactic acid microplastics: Evidence from unplanted vs. maize-planted microcosms - Jie Gao; En Guan; Zhiyu Zhang; Lichao Fan; Jinxia Xia; Yuyi Yang; Wenfeng Wang (Journal of Hazardous Materials, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

AI-driven thermal comfort management in public waiting halls: Passive sensing and adaptive HVAC control - Tianqi Zhang; Dengjia Wang; En Li; Yongchao Zhai; Zhenbin Lai; Jianhua Fan (Building and Environment, 2026)

IL-8/CXCR2 mediates resistance to apatinib through PI3K/AKT and vasculogenic mimicry in gastric cancer cells - Yan-Wen Fan; Ya-Xian Liu; Ning-Jing Jiang; Si-Tong Qian; Xin-En Huang; Jia-Qi Wu; Ming-Fang He (Tissue and Cell, 2026)

Biocontrol potential of estuarine bacterium Pseudoalteromonas sp. S-2: algicidal activity and mechanism against Microcystis aeruginosa - Ning Ding; Qian-En Zhu; Fan-Qiang Yan; Zheng-Qi Wang; Yu-Hao Song; Chao Wang; Ying Wang; Yu-jiao Ma; Pei-Ke Gao; Ren-Jun Wang (Biocatalysis and Agricultural Biotechnology, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Predictive modeling of high-speed ice-structure interaction using PD-AE-LSTM - Ming He; Mengshan Xie; Yu Ao; Xinran Li; En-Fan Lin (Ocean Engineering, 2026)

Efficient inactivation of UV resistant bacteria in reclaimed water by combined disinfection - Ke-Fan Cao; Zhuo Chen; En-Jing Wei; Bang-Hao Huang; Kai-Hong Lyu; Yu-Jia Gao; Yin-Hu Wu; Hong-Ying Hu (Journal of Water Process Engineering, 2026)

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Tailoring anchoring functionalities of self-assembled materials for efficient wide-bandgap perovskite solar cells - Zhong-En Shi; Yu-Fan Fu; Bo-Shun Peng; Ting-Chun Hung; Deebakkrishnan Ganesan; Rajendiran Balasaravanan; Shao-Huan Hong; Cheng-Liang Liu; Chun-Jen Su; Ming-Chou Chen; Chih-Ping Chen (Chemical Engineering Journal, 2025)

Progress in the application of DIC technology to rock mechanics testing: a review - Hao-fan Luo; Yang Tang; Wen-tao Feng; Jian-feng Liu; Hua Li; En-ze Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Bifunctional magnetic Fe/Fe3O4@Fe-N-C core-shell catalysts for external magnetic field-assisted enhancement of microbial fuel cell performance - Hai-Xia Liao; Dong-Ni Ou; Fan-Li Xiao; En-Xi Ruan; Nan Li (Science of The Total Environment, 2025)

Engineered Plasmonic multi-hot spots on magnetic Nanospheres for quantitative detection of pesticide residues on food surfaces via SERS tagging analysis - Ming-Jie Wan; Yu-Ting Wu; Yan-Hui Wang; Xiao-Hang Wu; En-Ming You; An Wang; Sheng-Hong Liu; Jin-Chao Chen; Yue-Jiao Zhang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Regulating charge separation by structure adjusting in pyrene-based 1D COFs for efficient photocatalytic hydrogen evolution - Bing Han; Shuyan Wang; Xianglin Yu; Xuxin Fan; En Liang; Yao Yang; Huan Zhang; Changyu Qin; Junbo Li (Chemical Engineering Journal, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

Mitigating quinolones contamination using Cyanophyta, Chlorophyta, and Bacillariophyta: Removal efficiency, degradation pathways and products - Yang Liu; Jiaxin Sui; Xinrui Fan; Tianli Zhang; Manogaran Lakshmikandan; Changshun Sun; En Hu; Ming Li (Journal of Water Process Engineering, 2025)

3D hot spot construction on the hydrophobic interface with SERS tags for quantitative detection of pesticide residues on food surface - Yan-Hui Wang; Chen Huang; Xiao Wu; Xiao-Feng Liu; En-Ming You; Sheng-Hong Liu; An Wang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Tissue distribution and residue depletion of difloxacin in crucian carp (Carassius carassius) after multiple oral administration - Fan Yang; Kai-Li Ma; Yue Liu; Yang-Guang Jin; Yan-Ni Zhang; Yan Dai; Ming-Hui Duan; Ze-En Li; Fang Yang (Aquaculture, 2024)

The Role of Benthic TA and DIC Fluxes on Carbon Sequestration in Seagrass Meadows of Dongsha Island - Lan-Feng Fan; En-Cheng Kang; Mariche B. Natividad; Chin-Chang Hung; Yung-Yen Shih; Wei-Jen Huang; Wen-Chen Chou (Journal of Marine Science and Engineering, 2024)
Coastal blue carbon ecosystems sequester carbon, storing it as plant biomass and particulate organic matter in sediments. Recent studies emphasize the importance of incorporating dissolved inorganic and organic forms into carbon assessments. As sediment-stored organic matter decomposes, it releases dissolved inorganic carbon (DIC) and total alkalinity (TA), both of which are critical for regulating the partial pressure of CO2 (pCO2) and thus carbon sequestration. This study investigated the role of benthic DIC and TA fluxes in carbon sequestration within seagrass meadows in Dongsha Island’s inner lagoon (IL) during the winter and summer seasons. Chamber incubation experiments revealed elevated benthic DIC and TA fluxes compared to global averages (107 ± 75.9 to 119 ± 144 vs. 1.3 ± 1.06 mmol m−2 d−1 for DIC, and 69.7 ± 40.7 to 75.8 ± 81.5 vs. 0.52 ± 0.43 mmol m−2 d−1 for TA). Despite DIC fluxes being approximately 1.5 times higher than TA fluxes, water pCO2 levels remained low (149 ± 26 to 156 ± 18 µatm). Mass balance calculations further indicated that benthic DIC was predominantly reabsorbed into plant biomass through photosynthesis (−135 to −128 mmol m−2 d−1). Conversely, TA accumulated in the water and was largely exported (−60.3 to −53.7 mmol m−2 d−1), demonstrating natural ocean alkalinity enhancement (OAE). This study highlights the crucial role of IL seagrass meadows in coastal carbon sequestration through net autotrophy and carbonate dissolution. Future research should explore the global implications of these processes and assess the potential of natural OAE in other coastal blue carbon ecosystems.

Ecological factors regulate stalk lodging within dense planting maize - Fanlei Kong; Fan Liu; Xiaolong Li; Pijiang Yin; Tianqiong Lan; Dongju Feng; Bi Song; En Lei; Zhong Li; Xinglong Wang; Jichao Yuan (Field Crops Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Internal dry reforming of methane in solid oxide fuel cells - Saeed Moarrefi; Mohan Jacob; Chao’en Li; Weiwei Cai; Liyuan Fan (Chemical Engineering Journal, 2024)

Optimized air-ground data fusion method for mine slope modeling - Dan Liu; Man Huang; Zhigang Tao; Chenjie Hong; Yuewei Wu; En Fan; Fei Yang (Journal of Mountain Science, 2024)

Mixing states and secondary formation processes of organic nitrogen-containing single particles in Guangzhou, China - Lijun Yun; Chunlei Cheng; Suxia Yang; Zaihua Wang; Mei Li; Qi En Zhong; Liyuan Mao; Sulin Liu; Xiaoya Cheng; Duanying Chen; Fan Yang; Zhen Zhou (Journal of Environmental Sciences, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

An Integrated Framework with ADD-LSTM and DeepLabCut for Dolphin Behavior Classification - Shih-Pang Tseng; Shao-En Hsu; Jhing-Fa Wang; I-Fan Jen (Journal of Marine Science and Engineering, 2024)
Caring for dolphins is a delicate process that requires experienced caretakers to pay close attention to their behavioral characteristics. However, caretakers may sometimes lack experience or not be able to give their full attention, which can lead to misjudgment or oversight. To address these issues, a dolphin behavior analysis system has been designed to assist caretakers in making accurate assessments. This study utilized image preprocessing techniques to reduce sunlight reflection in the pool and enhance the outline of dolphins, making it easier to analyze their movements. The dolphins were divided into 11 key points using an open-source tool called DeepLabCut, which accurately helped mark various body parts for skeletal detection. The AquaAI Dolphin Decoder (ADD) was then used to analyze six dolphin behaviors. To improve behavior recognition accuracy, the long short-term memory (LSTM) neural network was introduced. The ADD and LSTM models were integrated to form the ADD-LSTM system. Several classification models, including unidirectional and bidirectional LSTM, GRU, and SVM, were compared. The results showed that the ADD module combined with a double-layer bidirectional LSTM method achieved high accuracy in dolphin behavior analysis. The accuracy rates for each behavior exceeded 90%.

Characteristics of inorganic acid emission from various generation semiconductor manufacturing factories - Ming-Peng Yeh; Lian-Fang Wu; En-Tsu Fan; Tony Chen; Tzu-Sou Chuang; Sher Ling Lee; Kuo-Lun Tung (Chemosphere, 2024)

The lack of homology domain and leucine rich repeat protein phosphatase 2 ameliorates visual impairment in rats with diabetic retinopathy through regulation of the AKT-GSK-3β-Nrf2 signal cascade - Li Chen; En Qi; Xuan Liu; Lijun Cui; Xiaojuan Fan; Ting Wei; Yaguang Hu (Toxicology and Applied Pharmacology, 2024)

Sensitivity analysis and process optimization for biomass processing in an integrated gasifier-solid oxide fuel cell system - Hafiz Hamza Faheem; Ben Britt; Mateus Rocha; Shou-Han Zhou; Chao'en Li; Weiwei Cai; Liyuan Fan (Fuel, 2024)

Synthesis of magnetic bentonite–gelatin hydrogel beads and their applications in Cu2+ capturing - Qiang Shen; Tao Wu; Guo-Bang Zhang; Hao-En Ma; Wei Wang; Guo-Xiang Pan; Yi-Fan Zhang (Environmental Science and Pollution Research, 2023)

Rethinking personal carbon trading (PCT) mechanism: A comprehensive review - Yun-En Tang; Ru Fan; Ang-Zu Cai; Le-Yi Wang; Rui-Min Lin; Xiang-Zhou Meng; Ling Chen; Ru Guo (Journal of Environmental Management, 2023)

Causal effects of maternal exposure to PM2.5 during pregnancy on depression symptoms in adolescence: Identifying vulnerable windows and subpopulations in a national cohort study - Ke Ju; Liyong Lu; Zhikang Wang; Chenyu Yang; Ting Chen; En Zhang; Fan Tian; Jay Pan (Environmental Research, 2023)

Thermal preconditioning can reduce the incidence of intraoperatively acquired pressure injuries - Ping Hou; Huiping Xue; Shuwen Chang; Ping Xie; Yajie Chen; Yanwei Wang; Daiji Miura; Jianglin Fan; Jingyan Liang; Akio Kitayama; Fang Fang; Haijuan Yuan; et al. (Journal of Thermal Biology, 2023)

Using fluorescence index (FI) of dissolved organic matter (DOM) to identify non-point source pollution: The difference in FI between soil extracts and wastewater reveals the principle - Yuye Lin; En Hu; Changshun Sun; Ming Li; Li Gao; Linhua Fan (Science of The Total Environment, 2023)

Fast and accurate prediction of air temperature and velocity field in non-uniform indoor environment under complex boundaries - Yongqiang Luo; De'en Cui; Yixiao Song; Zhiyong Tian; Jianhua Fan; Ling Zhang (Building and Environment, 2023)

Semi-analytical modeling of large-scale water tank for seasonal thermal storage applications - Yongqiang Luo; De'en Cui; Lei Hu; Fabian Ochs; Alice Tosatto; Guozhi Xu; Zhiyong Tian; Abdulrahman Dahash; Jinghua Yu; Guofeng Yuan; Yaowen Chen; Dengjia Wang; et al. (Energy and Buildings, 2023)

Differences in evaporite geochemistry of the greater Ordos Ordovician salt basin, China: evidence from the M56 submember of the Majiagou Formation - Fu Fan; Fan-Wei Meng; Yong-Sheng Zhang; Mian-Ping Zheng; Kui Su; En-Yuan Xing (Carbonates and Evaporites, 2020)

A novel putative betapartitivirus isolated from the plant-pathogenic fungus Rhizoctonia solani - Yi Chen; Jia En Su; Xi Yun Qin; Zhi Yong Fan; Xiao Hai Zhang; Qing Yu; Zhen Yuan Xia; Cong Ming Zou; Gao Kun Zhao; Zhong Long Lin (Archives of Virology, 2020)

Filler improvement and purification effects of constructed rapid infiltration facility - Rui-song Zhao; Jia-ke Li; Chao Guo; Fan Li; Huai-en Li (Environmental Science and Pollution Research, 2019)

CNOT3 contributes to cisplatin resistance in lung cancer through inhibiting RIPK3 expression - Lin Jing; Meng-En Zhai; Jian Cui; Xin-Yu Fan; Yuan-Yuan Cheng; Jian-Li Jiang; Zhi-Nan Chen (Apoptosis, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Lateral wave-field stacking of seismic Fresnel zones for the generalized-offset case - Nan Tian; Ting-En Fan; Zong-Jun Wang; Wen-Tao Cai (Applied Geophysics, 2015)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Application of a web-based remote agro-ecological monitoring system for observing spatial distribution and dynamics of Bactrocera dorsalis in fruit orchards - Joe-Air Jiang; Tzu-Shiang Lin; En-Cheng Yang; Chwan-Lu Tseng; Chia-Pang Chen; Chung-Wei Yen; Xiang-Yao Zheng; Chun-Yi Liu; Ren-Hau Liu; Yu-Fan Chen; Wan-Yi Chang; Cheng-Long Chuang (Precision Agriculture, 2013)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Relationship between temperature change and the requirement for a permanent pacemaker implantation in bradyarrhythmias - I-Fan Liu; Shih-Lin Chang; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Chi-Woon Kong; Tsu-Juey Wu; Chern-En Chiang; Shih-Ann Chen; Yenn-Jiang Lin (International Journal of Biometeorology, 2011)

Parallel synthesis of natural product-like polyhydroxylated pyrrolidine and piperidine alkaloids - Yi-Fan Chang; Chih-Wei Guo; Ting-Hao Chan; Yi-Wen Pan; En-Lun Tsou; Wei-Chieh Cheng (Molecular Diversity, 2011)

Cloning, molecular characterization and expression analysis of a SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE gene (CitSERK1-like) in Valencia sweet orange - Xiao-Xia Ge; Gai-En Fan; Li-Jun Chai; Wen-Wu Guo (Acta Physiologiae Plantarum, 2010)

Highly efficient transformation of the GFP and MAC12.2 genes into precocious trifoliate orange (Poncirus trifoliata [L.] Raf), a potential model genotype for functional genomics studies in Citrus - Bin Tan; Ding-Li Li; Shi-Xiao Xu; Gai-En Fan; Jing Fan; Wen-Wu Guo (Tree Genetics & Genomes, 2009)

Molecular cloning and characterization of the promoter for the multiple stress-inducible gene BjCHI1 from Brassica juncea - Xue-Feng Wu; Chun-Lian Wang; En-Bei Xie; Ying Gao; Ying-Lun Fan; Pi-Qing Liu; Kai-Jun Zhao (Planta, 2009)